IMPACT OF PRINCIPAL SITUATIONAL LEADERSHIP STYLE ON THE TEACHERS’ JOB PERFORMANCE AT SECONDARY SCHOOL LEVEL - Irtaza Hassan; Yasir Mustafa; Samina; Dr. Safia Noor; Dr. Faheem Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study focused on the impact of principal situational leadership style on the teachers’ job performance at secondary school level. The research philosophy of positivism was applied. Thus, the researcher employed a survey research design was employed. A sample of 347 Secondary School Teachers (SSTs) was selected through stratified sampling method. A questionnaire was used in which items were related to situational leadership and teachers’ performance. Content Validity Index (CVI) and Cronbach Alpha were used to estimate the content validity and reliability of the instrument respectively. Pearson Product Correlation, linear regression and t-test was used to test the formulated hypotheses. The study concluded that situational leadership has significant impact on the teachers’ performance. The study recommended that the practice of situational leadership should be performed to enhance the teachers performance.